ANALISIS KUALITAS KLUWEK (Pangium edule Reinw) HASIL FERMENTASI MENGGUNAKAN MEDIA TANAH DAN ABU SEKAM - Elite Gizwati Samudry; Andi Sukainah; Amirah Mustarin (Jurnal Pendidikan Teknologi Pertanian, 2017)
This research aims to look at the effect using media of fermentation and period for fermentation to the quality of kluwek. The experimental design used was completely randomized factorial designed (factorial RAL). Media of fermentation is used soil and ash husk with period of fermentation is 40 days, 50 days and 60 days. Parameters measured were contained cyanide levels in kluwek fermented and contains other nutrients such as water content, ash content and protein content. The best research are fermentation of  kluwek using  husk ash with period of fermentation 60 days, with level of cyanide reached 0.04 µg/g. And has a water content of 59.6%, ash content 2.59%, and protein content 22.07%